Avaliação da corrosão intergranular de aços inoxidáveis por meio de normas e de ensaios eletroquímicos em altos potenciais - Higa, Silvia Midori (Universidade Federal de São Carlos, 2011)
The corrosion resistance of stainless steels is given by the formation of a Cr2O3 film on the metal surface, inhibiting its contact with the aggressive medium. The sensitization that occurs in these steels at temperatures ranging from 500 to 800°C is responsible for corrosion due to carbide precipitation at grain boundaries, which makes the adjacent regions depleted of chromium. The standards used in industries to assess the stainless steels in their susceptibility to corrosion is based on immersion tests followed by microstructural analysis. The electrochemical tests provide a deeper analysis of the degree of sensitization that is often not detected by tests of immersion. This study aimed to evaluate the different techniques to determine the susceptibility to localized corrosion, pitting and intergranular in stainless steels to sensitization at different temperatures and compare them with current standards. Were used austenitic stainless steel AISI 304, AISI 304L, AISI 316L and martensitic stainless steel AISI 420. The evaluation of corrosion was carried out by potentiodynamic reactivation tests and double-loop cyclic anodic polarization, besides the classification according to the criteria of ASTM A 262 practice A. The electrochemical tests have provided a further analysis based on the standard immersion tests. The degree of sensitization obtained in the electrochemical tests showed an impairment of corrosion resistance of stainless steels, which, according to the criteria of the standard would be accepted for susceptibility to intergranular corrosion.
Assessment of intergranular corrosion of stainless steel by means of testing and standards electrochemical in high potential
Keywords: Corrosão; Aço inoxidável; Resistência à corrosão; Corrosão por pites; Ensaios eletroquímicos; Stainless steel; Pitting corrosion; Electrochemical tests; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA